Larvicidal Effect of Mixture of Beauveria bassiana Crude Metabolite and Chitinase Enzyme against Aedes aegypti Larvae - Widiastuti, Dyah; Ikawati, Bina; Hadi, Upik Kesumawati (UI Scholars Hub, 2018)
Aedes aegypti is a major vector of dengue, a deadly disease causing deaths of millions of people in developing countries, both in urban and rural populations. Aedes aegypti control with chemical insecticide is widely used, and affects on a widespread insecticide resistance. Mosquito biological control was needed to replace the use of chemical insecticide. This study aimed to evaluate larvicidal effect of mixture of Beauveria bassiana crude metabolite and chitinase enzyme against Aedes aegypti larvae. An experimental study using completely Randomized Design was conducted in March-April 2016 at Banjarnegara Research and Development Unit for Zoonosis Control. Biolarvacide formula was made of mixture with 2 : 1 ratio between Beauveria bassiana crude metabolite and chitinase isolated from chitinolytic bacteria, which was propagated by the Agency’s Bacteriology Laboratory. In experimental method, 120 Aedes aegypti larvae (3rd instar) were exposed with four concentrations of biolarvacide formula (4%, 8%, 16%, and 32%) in 3 replicates. Results showed that exposure of biolarvacide formula caused the third instar larval mortality which started on the first day of exposure. Probit analysis showed LC50 value was obtained at concentration of 53.2 ppm. This shows that larvacide formula of Beauveria bassiana and chitinase enzyme compounds are effective to be used as larvacides against Aedes aegypti larvae.